Gangliocytic paraganglioma: a rare case with metastases of all 3 elements to liver and lymph nodes. - Rowsell, C; Coburn, N; Chetty, R (2011)
Gangliocytic paragangliomas are a rare but well-described neuroendocrine tumor with a proclivity for the duodenal area. It is usually a locally infiltrative lesion with a good prognosis. Rare cases that spread to lymph nodes have been documented. A 52-year-old female was found to have a duodenal tumor, enlarged regional lymph nodes, and multiple small nodules in the liver. The duodenal tumor was a classic triphasic gangliocytic paraganglioma. Two regional lymph nodes and one of the nodules in the liver were noted to contain all 3 elements constituting a gangliocytic paraganglioma. This is the second case of gangliocytic paraganglioma with liver spread and is also noteworthy because of the presence of all 3 elements in the metastases. The presence of lymph node and liver metastases should not result in overtreatment as such behavior is not necessarily fraught with a bad clinical outcome. It is probably best to regard such cases as having "uncertain malignant potential" and advocate careful follow-up.